Fast and quantitative manganese sorption by polyamidoamine resins. Issue 4 (27th November 2012) - Manfredi, Amedea; Ranucci, Elisabetta; Morandi, Sara; Mussini, Patrizia Romana; Ferruti, Paolo
<x xml:space="preserve">Abstract</x> Two poly(amidoamine) crosslinked resins whose repeating units are mimics of L‐lysine (LYMA) and of EDTA (LMT85) prove capable of quantitatively and reversibly sorbing manganese ions (Mn2+). Halving times are on the order of 1 min or less, and Mn2+ can be abated to the ppb level. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>